Balance Sheet Analysis in Fund Surveillance. (Policy Papers; Policy Paper, 2015)
Balance sheets convey vital information about economic prospects and risks. Balance sheet analysis captures the role that financial frictions and mismatches play in creating fragility and amplifying shocks. This is key to understanding the macroeconomic outlook, identifying vulnerabilities, and tracing the transmission of potential shocks and policies. This paper reviews the use of balance sheet analysis in the Fund's bilateral surveillance and introduces some practical examples of how it can be deepened. Recent evaluations of IMF surveillance--including the 2014 TSR--have emphasized the importance of strengthening balance sheet analysis and coverage of macro-financial issues. This paper is a first step that highlights useful examples of such analysis conducted by staff over the last decade, documents the data and tools that have been used, and mentions some limitations. In addition, it discusses recent improvements in the coverage and quality of balance sheet data through initiatives launched in the wake of the global crisis, as well as key remaining gaps, addressing which requires international collaboration.